Using periodic point‐prevalence surveys to assess appropriateness of antimicrobial prescribing in Australian private hospitals. Issue 3 (March 2014) - Cotta, M. O.; Robertson, M. S.; Upjohn, L. M.; Marshall, C.; Liew, D.; Buising, K. L.
Abstract Background and Aims Appropriateness of antimicrobial use is a measure of key importance in evaluating safety and quality of prescribing but has been difficult to define and assess on a wide scale. Published work is limited and has generally focused on tertiary public hospitals, whereas the private sector provides a significant proportion of care in many countries. Information on prescribing in the private hospital context is needed to identify where intervention might be required. An antimicrobial prescribing survey tool was utilised to assess the appropriateness of antimicrobial prescribing among large private hospitals in Australia. Methods 'Appropriateness' of antimicrobial therapy was evaluated by a team consisting of an infectious diseases physician and specialist infectious diseases pharmacist based on clear criteria. Results Thirteen hospital‐wide point‐prevalence surveys were conducted. Three thousand, four hundred and seventy‐two inpatient medication charts were reviewed to identify 1125 (32.4%) inpatients on 1444 antimicrobials. An indication was documented in 911 (63.1%) of surveyed prescriptions, and overall, 757 (52.4%) of antimicrobials were assessed as appropriate. Antimicrobials prescribed for treatment had a higher proportion of appropriateness when compared with antimicrobials prescribed for surgical prophylaxis (80.4% vs 40.6%). The main reason for a treatment prescription to be considered inappropriate was incorrect selection, while prolonged duration (>24 h) was the main reason for inappropriate surgical prophylaxis prescriptions. Conclusions This study provides important data on antimicrobial prescribing patterns in Australian private hospitals. Results can be used to target areas for improvement, with documentation of indication and surgical antibiotic prophylaxis requiring initial attention.